(untitled) (Revista Brasileira de Contabilidade e Gestão, 2022)
The general objective of the study was to identify the benefits and difficulties of the digital age in the perception of accounting professionals in Fortaleza / CE. To this end, a quantitative survey was applied that used data collected through a survey applied to 124 accounting professionals. Thus, in the data analysis, descriptive statistics, exploratory factor analysis (EFA) and Kruskal-Wallis mean test were applied. The results signaled that, among the benefits provided by the digitalization of the accounting area, the most highlighted by the professionals was the promotion of greater consistency and reliability in the issuance of bookkeeping, while the most pointed difficulties were the lack of data or incomplete data. Thus, it stands out that, as accounting professionals recognize the advances brought by digitalization, there is still much to be done in terms of simplifying and improving systems, routines, including their own technical capacity.